2017
DOI: 10.1016/j.bbmt.2017.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Cell Transplantation for Adult Chronic Myelomonocytic Leukemia

Abstract: Allogeneic hematopoietic cell transplantation (HCT) is potentially curative for patients with chronic myelomonocytic leukemia (CMML), however, few data exist regarding prognostic factors and transplant outcomes. We performed this retrospective study to identify prognostic factors for post-transplant outcomes. The CMML-specific prognostic scoring system (CPSS) has been validated in subjects receiving non-transplant therapy and was included in our study. From 2001–2012, there were 209 adult subjects who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 41 publications
2
36
1
Order By: Relevance
“…Results in CMML patients treated with allo-HSCT depend on the pre-transplant risk scores (HCT-specifi c CPSS), as shown by IBMTR group in 209 patients [16]. I.e., adjusted disease-free survival, starting at the time of transplant, at a median follow-up of 51 months.…”
Section: Chronic Myelomonocytic Leukemia (Cmml)mentioning
confidence: 99%
“…Results in CMML patients treated with allo-HSCT depend on the pre-transplant risk scores (HCT-specifi c CPSS), as shown by IBMTR group in 209 patients [16]. I.e., adjusted disease-free survival, starting at the time of transplant, at a median follow-up of 51 months.…”
Section: Chronic Myelomonocytic Leukemia (Cmml)mentioning
confidence: 99%
“…A single‐institution study found advanced age, increased HCT comorbidity index and adverse‐risk cytogenetics to have an independent adverse prognostic impact with greater mortality and decreased relapse‐free survival . Retrospective data from Center for International Blood and Marrow Transplant Research validated the CPSS‐prognostic system in 209 CMML patients who were treated with HSCT, and found Karnofsky performance status, graft source and CPSS score to be independent predictors of survival in a multivariable model . Recently in MDS, mutation clearance detected in the bone marrows 30 days after allogeneic HSCT, correlated with a lower risk of disease progression .…”
Section: Disease Biology and Genomic Abnormalitiesmentioning
confidence: 99%
“…Attempts to statistically evaluate prognostic impacts on post-transplant outcomes among patients with aCML were unsuccessful due to the small number of patients in the present study. We stratified OS after transplantation by the prognostic factors previously identified for aCML itself and MDS/MPN other than aCML [7,[41][42][43][44][45][46][47][48][49]: age at transplantation, the Karnofsky Performance Status (KPS), blast percentages in peripheral blood, white blood cell counts, hemoglobin levels, transfusion dependency, karyotype, the presence of splenomegaly, type of donor source, donor/recipient sex match, and the interval from the initial diagnosis to allo-HSCT. Regarding aCML, 1-year OS were 80.0% (95% CI, 20.4 to 96.9%) and 44.4% (95% CI, 13.6 to 71.9%) in patients using HLAmatched-related (n=5) and alternative donors (i.e.…”
Section: Disease Responses and Survival Analysismentioning
confidence: 99%